Non-Ampullary Duodenal Tumors - Yeonjin Je; Young Hoon Youn (Yong Chan Lee, 2022)
Non-ampullary duodenal tumors refer to duodenal lesions that originate at sites other than the ampulla of Vater. They differ from ampullary duodenal tumors, which are typically associated with obstructive symptoms. Non-ampullary duodenal tumors are rare; therefore, standardized clinical management, including diagnostic and therapeutic modalities and the follow-up strategy remain unclear. An increase in the numbers of patients undergoing endoscopy during medical checkups and technological advances in endoscopic procedures, including high-resolution and image-enhanced endoscopy have led to an increase in detection rates of duodenal tumors recently. Currently, endoscopic resection of duodenal tumors is widely used and is a preferred therapeutic alternative to surgical excision. Some duodenal tumors of high malignant potential are associated with poor prognosis; therefore, accurate diagnosis and timely management are important. In this article, we review the current knowledge regarding non-ampullary duodenal tumors and the therapeutic approaches to these lesions.